PENGGUNAAN GLUKOMANAN DARI UMBI PORANG (Amorphophallus oncophyllus Pr.) SEBAGAI BIODEGRADABLE FILM DENGAN PENAMBAHAN SORBITOL DAN GLISEROL SEBAGAI PLASTICIZER - Sudarsono, Agustina Putri Pitarisa; Sari, Clara Evita; Ayuningtyas, Nurista Dida (Jurnal Farmasi & Sains Indonesia, 2023)
Plastic waste that is not handled properly will cause disaster. Glucomannan is a type of hemicellulose polysaccharide from porang flour with an extraction method to extract glucomannan compounds in porang flour. The addition of plasticizer as an additive is useful for forming a film layer in this study. Biodegradable film is a type of film coating as a food wrapper that is environmentally friendly and safe to eat which can be decomposed by microorganisms made from processed starch compounds. Porang tubers have the potential as a biodegradable film material with high glucomannan content. This study aims to make a biodegradable film from Porang tubers and to determine the performance of sorbitol and glycerol as plasticizers. The research method begins with the extraction of porang flour with 50% and 80% ethanol twice in a ratio (1:6) stirred using a homogenizer for 30 minutes, then to form a biodegradable film with the addition of sorbitol and glycerol plasticizers using a magnetic stirrer for 45 minutes. minutes with a stirring temperature of 80ºC followed by an evaluation of the biodegradable film characterization, swelling test, FTIR test, biodegradation test using One Way Anova statistical analysis. The results showed that the biodegradable film with the addition of 10% glycerol plasticizer showed good results with the characteristics of the biofilm being slightly viscous, the evaluation degree of swelling was 76.13%, degraded for 20 days.